2021
DOI: 10.1021/acsami.1c06634
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Conductive Networks Built by Prussian Blue Cubes and Mesoporous Carbon Lead to Enhanced Sodium-Ion Storage Performances

Abstract: The challenges of improving electrical conductivities and enhanced rapid dynamics are active research areas in the modification of Prussian blue (PB) and Prussian blue analogues (PBAs), which are used as excellent cathodes of sodium-ion batteries (SIBs). Herein, the terephthalic acid etched stepwise hollow bulky PB cubes and the intimate contact mesoporous carbon (CMK-3) particles with the adhered minisize PB cubes can together build continuous conductive networks. The composite (donated as N-PB@CMK) has high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…43 The weak peaks of the oxidation process at ∼4.0 V, which gradually disappeared, exhibit the formation of a solid electrolyte interphase (SEI). 43,44 Furthermore, W-PB showed poor cycling stability, given that the specific discharge capacity decreased to ∼50 mAh g −1 after 500 cycles at 150 mA g −1 , while I-PB could retain ∼90 mAh g −1 (Figure 2g). More importantly, I-PB shows a higher capacity retention of 64.9% over ∼3000 cycles at a high current density of 750 mA g −1 with Coulombic efficiency (CE) of ∼100% (Figure 2h), corresponding to a low capacity fading of 0.01% per cycle.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…43 The weak peaks of the oxidation process at ∼4.0 V, which gradually disappeared, exhibit the formation of a solid electrolyte interphase (SEI). 43,44 Furthermore, W-PB showed poor cycling stability, given that the specific discharge capacity decreased to ∼50 mAh g −1 after 500 cycles at 150 mA g −1 , while I-PB could retain ∼90 mAh g −1 (Figure 2g). More importantly, I-PB shows a higher capacity retention of 64.9% over ∼3000 cycles at a high current density of 750 mA g −1 with Coulombic efficiency (CE) of ∼100% (Figure 2h), corresponding to a low capacity fading of 0.01% per cycle.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…17 In fact, many oxide materials have been explored as electrodes for SIBs including layered and polyanionic structures as well as Prussian blue having high theoretical capacity, and cycling stability, as well as high operating potentials. [18][19][20][21][22][23][24][25][26][27] However, in order to improve the electrochemical performance of SIBs for practical use in energy storage devices, one should focus on achieving high specic capacity and a high working potential simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…PB NPs formed a dark blue suspension (Figure S1, Supporting Information), and TEM imaging showed that the synthesized PB NPs were cubic particles ( Figure a). XRD analysis (Figure S2, Supporting Information) of PB NPs revealed characteristic peaks at 2θ = 17.45, 24.78, 35.33, 39.66, 43.63, 50.82, 54.15, and 57.34, which were assigned to the crystal faces (200), (220), (400), (420), (422), (440), (600), and (620) of the face‐centered cubic Fe 4 [Fe(CN) 6 ] 3 crystal (PDF# 73–0689), [ 38 ] which fully confirmed that we successfully synthesized PB NPs. PB‐PFP@PC was synthesized using the modified double‐emulsion method, in which PB NPs and PFP were encapsulated into the core‐shell structure of PLGA.…”
Section: Resultsmentioning
confidence: 99%